An Effectiveness of Empowering Leadership on Employees and their Productive Voice Behavior: Empirical Study on Mediating role of Psychological safety and Leader Member Exchange - Vavilapall, Sivajee; Datta, Auadhati (International Journal of Psychosocial Rehabilitation, 2020)
The relationship between empowering leadership and employee voice behavior and the role of psychological safety and LMX (Leader member exchange) as mediators is the same. The study utilizes structural equation modeling for analyzing the data collected from Indian service industry employees through the questionnaire developed for the study. The study demonstrates the significant impact of empowering form of leadership on employees’ constructive voice behavior. By supporting results were observed for the mediating impact of leader member exchange (LMX) and psychological safety between empowering leadership and employees’ constructive voice behavior. Intervening mechanisms by linking leaders’ empowering behavior with employees’ constructive voice, while also highlighting the potential importance of LMX relationship in organizations and psychological safety in context of constructive voice behavior. The piece of work is assumed to benefit the leaders in organizations by providing them the basis for adopting empowering form of leadership in light of results displayed and its revealed impact on the constructive voice behaviour. The study brings forth the relevance of quality LMX for promotive constructive voice behaviour in the organization. The study establishes the new form of leadership, ‘empowering leadership’ for fostering the better exchange of ideas, opinions, and suggestions between leaders and followers which tend to benefit the organization, providing empirical evidence of the sequential mediation of LMX and psychological safety.